PERISTILAHAN SATUAN UKURAN DALAM BAHASA DAYAK NTUKA KECAMATAN NANGA TAMAN KABUPATEN SEKADAU - Goreti, Maria; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractDayak Ntuka is one of the Dayak sub-tribes who live in the Nanga District of Sekadau District. Local wisdom contained in the unit of measurement in the Dayak Ntuka is a distinctive characteristic of other Dayak sub-tribes. Unit is a tool used to express measurement results, standard or basic size. Therefore, in Indonesian the unit of measurement used is gram, kg, ounce, ton, meter, and cm, i n Dayak Ntuka there are also various kinds of words which state unit length, number, unit of content, unit and weight. The unit of measure serves to measure the quantity of an object, the unit of measure also has the meaning and value that we can find in the Dayak Ntuka Language. The traditional unit of measure has a meaning that has aspects of culture and culture of the people who own the culture so that the traditional unit of measure is maintained. The study was conducted in Pantok Village which is a native speaker of the Dayak Ntuka language. This study includes terminology, meaning, meaning, and Indonesian language learning texts in the 2013 curriculum education unit. Data analysis consists of four classifications, namely categories of terminology, words, phrases, lexical meanings, meanings, and meanings in units of measure. Keywords: Terminology, Size Unit, Dayak Ntuka